Le verrier-magnificent and detestable astronomer - Lequeux, James (Astrophysics and Space Science Library, 2013)
Le Verrier was a superb scientist. His discovery of Neptune in 1846 made him the most famous astronomer of his time. He produced a complete theory of the motions of the planets which served as a basis for planetary ephemeris for a full century. Doing this, he discovered an anomaly in the motion of Mercury which later became the first proof of General Relativity. He also founded European meteorology. However his arrogance and bad temper created many enemies, and he was even fired from his position of Director of the Paris Observatory.